Visible-to-near-infrared optical properties of protein, lipid and carbohydrate in both solid and solution state at room temperature. (January 2021) - Li, Xingcan; Xie, Bowei; Wu, Minghui; Zhao, Junming; Xu, Zhiming; Liu, Linhua
Highlights: Optical constants of protein, carbohydrate and lipid were experimentally determined. Isolations of protein, lipid and carbohydrate from Chlorella sp. were conducted. Fitted formula of the refractive index was presented. Abstract: An accurate knowledge of optical constant of protein, lipid and carbohydrate is important for analyzing radiative transport between cells. However, it is difficult to measure precisely the optical constant of these elements due to the complicated sample-making and the limitation of traditional measurement method. In this work, the double optical pathlength transmission method and the ellipsometry method (DOPTM-EM) were used to obtain the optical constants of protein, lipid and carbohydrate of Chlorella sp. (both solid-state and solution-state), solution-state egg protein and solution-state sucrose in the spectral range 300-1700 nm. Isolations of protein, lipid and carbohydrate from Chlorella sp. were conducted. For different types and states of protein, lipid and carbohydrate, the optical constants of these samples are different from each other. The refractive indices of protein and carbohydrate have obvious relationship with the existing state. A significant difference of absorption indices can be observed between the solution-state protein of Chlorella sp. and the egg protein. It is indicated that the amino acids composition of solution-state protein of Chlorella sp. differs from the egg protein. The absorption indices of solution-state carbohydrate do not agree with the solution-state sucrose. For the sake of applications, the fitted formula of the refractive index as a function of wavelength is presented.